Iowa Birdline update, March 25, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of the Iowa Birdline update for March 25, 1991. Highlights include early Eastern Phoebes, a Varied Thrush, a Cinnamon Teal and continued waterfowl migration. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed